Zinc fractions and Barley productivity under zinc fertilization and sodic irrigation water management - DOGRA, PRERNA; YADAV, B L; KUMAWAT, CHIRANJEEV; PARASHAR, AABHA; MEENA, G L (The Indian Journal of Agricultural Sciences, 2021)
An experiment was conducted to know the effect of different residual sodium carbonate (RSC) water, farmyard manure (FYM) and different levels of zinc fertilization on different zinc fractions of soil, yield attributes and yield of barley in loamy sand soil under semi-arid climatic conditions. The three levels of RSC of irrigation water (2.5, 5 and 10 mmol/ L), two levels of FYM (control and 15 t/ha) and four levels of zinc (control, 15, 30 and 45 kg ZnSO4/ha) were evaluated on barley production in split plots design. Results indicated that application of high RSC irrigation water (10 mmol/ L) significantly reduced the different fractions of soil Zn (except Occ-Zn), plant height, total and effective tillers, test weight and yield of barley during both the years, while 5 mmol/L of RSC irrigation level found at par with 2.5 mmol/L. Application of FYM significantly increased the different Zn fractions in soil (except Occluded- Zn) as well as yield attributes, grain and straw yield of barley. The increasing level of zinc application significantly increased the different fractions of soil Zn (except Occ-Zn), available soil Zn, yield attributes and yield of barley. It was observed that the grain yield of barley positive and significantly correlated with different fractions of Zn, viz. DTPA-Zn (r=0.888), Ads-Zn (r=0.525), Occ-Zn (r = 0.670), OC-Zn (r = 0.948) and Res-Zn (r = 0.923). The optimum dose of zinc for barley computed as 37.6 kg / ha ZnSO4 with corresponding optimum yield of 4365 kg/ha.